2020
DOI: 10.3390/antibiotics9080456
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sulfonamide Contamination Derived from Veterinary Antibiotics on Plant Growth and Development

Abstract: Veterinary antibiotics such as sulfonamides are widely used to increase feed efficiency and to protect against disease in livestock production. The sulfonamide antimicrobial mechanism involves the blocking of folate biosynthesis by inhibiting bacterial dihydropteroate synthase (DHPS) activity competitively. Interestingly, most treatment antibiotics can be released into the environment via manure and result in significant diffuse pollution in the environment. However, the physiological effects of sulfonamide du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 82 publications
1
14
1
Order By: Relevance
“…Although studies have investigated the off-target and toxicity effects of asulam, such as its inhibition of mammalian sepiapterin reductase (Yang et al, 2015b), its crosskingdom activity against soil microbiota is less well-studied (European Food Safety Authority et al, 2018). Sulfonamide antibiotics are used in the livestock industry and have been reported to have phytotoxic effects (Liu et al, 2009;Piotrowicz-Cieślak et al, 2010;Cheong et al, 2020). As we demonstrate the herbicidal potency of sulfamethoxazole against A. thaliana, a previous study showed it was herbicidal against duckweed (Lemna gibba) (Brain et al, 2008).…”
Section: Exploring Alternative Hppk/dhps Inhibitors As Herbicidessupporting
confidence: 59%
“…Although studies have investigated the off-target and toxicity effects of asulam, such as its inhibition of mammalian sepiapterin reductase (Yang et al, 2015b), its crosskingdom activity against soil microbiota is less well-studied (European Food Safety Authority et al, 2018). Sulfonamide antibiotics are used in the livestock industry and have been reported to have phytotoxic effects (Liu et al, 2009;Piotrowicz-Cieślak et al, 2010;Cheong et al, 2020). As we demonstrate the herbicidal potency of sulfamethoxazole against A. thaliana, a previous study showed it was herbicidal against duckweed (Lemna gibba) (Brain et al, 2008).…”
Section: Exploring Alternative Hppk/dhps Inhibitors As Herbicidessupporting
confidence: 59%
“…Compared with (fluor)quinolones, sulphonamides mainly suppress microorganism growth and multiplication and act as a competitive inhibitor of the bacterial enzyme dihydropteroate synthetase (DPS), an enzyme involved in folate biosynthesis [ 107 ]. Tokanová et al [ 90 ] have showed that the exposure of zebrafish to sulfamethoxazole (50–500 μg/L) for 14 days has no significant impact on the antioxidant enzyme activity (e.g., glutathione peroxidase, glutathione reductase and glutathione S-transferase) compared to the control group.…”
Section: Effects Of Individual Antibiotics In Zebrafishmentioning
confidence: 99%
“…Due to the lack of folic acid, the synthesis of amino acids and nucleotides in the bacteria is blocked, resulting in bacteria being unable to grow and multiply. [244,245] Although some antibiotics have significant bactericidal effects, they are not the best choice for fighting infections due to their hydrophobicity, poor skin permeability, and systemic toxicity. [246] In addition, the emergence of drug-resistant bacteria significantly erodes the enthusiasm concerning antibiotics.…”
Section: Loading Antibioticsmentioning
confidence: 99%